Feasibility planning study of lattice radiotherapy for palliation in bulky tumors - Jayashree NP; Shreekripa Rao; Anshul Singh; Umesh Velu; Ankita Mehta; Shirley Lewis (Precision Radiation Oncology)
Abstract Purpose Lattice radiotherapy can potentially deliver high doses to the tumor core, while conventional doses to the periphery resulting in improved response rates in large tumors (> 5 cm). We assessed the feasibility of planning lattice radiotherapy and dosimetrically compared it with conventional radiotherapy. Methods This retrospective dosimetric study evaluated 10 patients with large tumors (> 5 cm) treated with palliative intent with a dose of 20Gy in five fractions. High‐dose lattice points were created at doses of 50Gy in non‐hepatic tumors and 35Gy in hepatic tumors. Lattice plans were compared with treatment plans regarding dose coverage and organ‐at‐risk dosimetry. Results Treated sites included soft tissue metastases to the neck, lungs, abdomen, pelvis, and liver. The mean lesion volume was 1103 cc (352–3173 cc). The maximum tumor size was 16 cm. The target volume coverage was > 95% in all but one case (88% to achieve organ constraints). Dosimetry and organ‐at‐risk doses were similar in both palliative treatment and simulated lattice plans. Conclusion Lattice radiotherapy is feasible in large tumors using volumetric‐modulated arc therapy and achieves good coverage while meeting organ constraints. However, a prospective clinical evaluation is required to confirm its efficacy.